Genospecies Diversity of Borrelia in Ixodes Ticks of the West Siberia - S. A. Rudakova; O. E. Teslova; N. E. Kaneshova; S. V. Shtrek; V. V. Yakimenko; N. A. Penyevskaya (Проблемы особо опасных инфекций, 2020)
Objective: to determine genospecies composition of Borrelia in the ixodid ticks of various species in natural foci of Ixodes tick-borne borreliosis (ITB) in the South of Western Siberia. Materials and methods. A total of 1148 examples of ticks collected from vegetation and 2183 examples of ticks withdrawn from persons seeking medical help have been tested by bacteriological (sowing in BSK-H medium, SIGMA, USA) and Real Time PCR methods. Genotyping of Borrelia was performed by sequencing. Results and conclusions. Infection of Ixodes ticks with borrelia ranged from 22.4 % in the Altay Republic to 56.9 % in the Novosibirsk Region. Reliable differences in borrelia infection rates of ticks I. persulcatus and I. pavlovskiy have not been established (average levels of infection 40 % and 38.8 %, respectively). The study of isolates of borrelia sp. circulating in natural foci of the West Siberia showed the presence of at least four genospecies of pathogenic borrelia (B. garinii, B. afzelii, B. bavariensis, B. miyamotoi). 30 nucleotide sequences of the rrf (5S)-rrl (23S) intergenic spacer were submitted to GenBank database. The detection rate of genospecies B. garinii and B. afzelii of different types of ticks (I. persulcatus and I. pavlovskiy) has no significant difference. More frequent occurrence of B. garinii in comparison with that of B. afzelii was determined. The level of I. persulcatus ticks infection with B. miyamotoi was significantly lower than that with genospecies B. garanii and B. afzelii. DNA of B. spielmanii and B. miyamotoi was detected in ticks D. reticulatus. Further evaluation of the role of ticks D. reticulatus in the distribution of borrelia in ticks in natural foci of the Russian Federation is necessary.